Detection of Phospholipase and Asparty1 Protaines gens in Candida Species Isolated From Mammary Candidiasis in Lactating Women - Abrar Mohammed Qneed Al-Dafay; Khairi Jameel AL-Ruaby; Alwan Abed Hamadi AlQushawi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Breast and nipple thrush (BNT) is a yeast infection of the nipple and breast caused by a fungal organism knownas Candida albicans, a common cause of all thrush infections. It occurs most commonly in breastfeedingmothers. The infection may lead to severe nipple and breast pain, especially during breastfeeding. Thecurrent study was conducted at Al-Kut hospital for Gynecology, obstetrics and pediatrics, and TaibaSpecialist Centerin Wasit province. (162) milk samples were collected from lactating wommen suspected tohave mammary candidiasis infections according to the clinical manifestations diagnosed by the examiningphysician and patient with symptom , then, the samples were examined by optical microscopy and celldetection which show evidence of the presence of pathogenic yeast. Samples were cultured in sabouraudagar and then in chrom agar to classify the organisms, and they were held for further conformation and todetect the most common virulence factor gen by polymerase chain reaction (PCR) Molecular identificationof Candida spp in this study, done by conventional PCR by partial amplification gene encoding for largesubunit of 18S rRNA gene by specific primer sequences. The yield of the detection C. albicans and C.parapsilosis, was 37/37(100%) (100%) and 15/15 (100%), respectively. The results of PCR amplificationof( SAP1-8)genes in Candida isolates (61) were SAP1 gen was present in 61/61(100%) , SAP2 gen was54/61(96%), SAP3 gen was 45/61(86%), SAP4 gen was 35/61(76%), SAP5 gen was 32/61(66%), SAP6 genwas 45/61(60%), SAP7 gen was 35/61(30%) and SAP8 gen was 21/61(34%). By molecular technique usingPCR (PLB1-2 gene) and sequencing, it was seen that Seventeen isolates belong C. albicans were positivefor PLB1 gene 17/61 (91.6%). Fourteen isolates belong C. albicans were positive for PLB1 gene 14/61.